What is at the Root of the American Global Crisis? - Ismail; Encup Supriatna; Moh. Dulkiah (GoAcademica Research & Publishing, 2019)
The rising defaults on subprime mortgages in the US triggered a global crisis for the money markets. The fact is the global financial crisis started with the US policies. What began with elevated losses on US subprime mortgages has spread beyond the borders of the United States and the confines of the mortgage market. Many of the world’s leading investment banks have collapsed as a result. Depression, a thing of the past, has made a striking comeback. Will it come back again in the future? Who is to blame? What should be done to avoid future incidence?